Nanoscale investigation of potential distribution in operating Cu(In,Ga)Se2 thin-film solar cells - Zhang, Zhenhao (KIT Scientific Publishing, 2013)
The distribution of the electrostatic potential in and between the materials in Cu(In,Ga)Se2 thin-film solar cells has a major impact on their superior performance. This thesis reported on the nanoscale imaging of the electrostatic potential on untreated cross sections of operating Cu(In,Ga)Se2 solar cells using Kelvin probe force microscopy.